COMMON TYPES OF DISTANCE LEARNING - Shoyimkulova Mahzuna Shavkatovna , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
As we know distance learning is conducted according to rules, it can be a real comfortable way of learning but if there are problem with technical equipment, the expected result cannot be achieved. Often considered to be the lesser cousin of regular education, distance education is often plagued by lack of enough good quality faculty members. The article analyzes the types of distance learning and their differentiation.